PERTUMBUHAN DAN HASIL PISANG MULI (Musa acuminata L.) DENGAN PEMBERIAN PUPUK ORGANIK GUANO - Norasyifah Norasyifah; Muhammad Ilyas Ilyas; Tuti Herlina Wati Wati; Kani Kani; Mahdiannoor Mahdiannoor (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
Banana plants are plants that from the roots to the leaves can be used for human purposes. But the quantity and quality of production is still low, to increase production, it needs special treatment with fertilization. In addition to being a banana producer, Balangan Regency also has the potential for guano fertilizer. The purpose of this study was (i) to find out the growth and yield of muli bananas by guano organic fertilizer (ii) to get the best dose of guano organic fertilizer for optimal growth and yield of muli banana. This research was conducted in Kambiyain Village, Tebing Tinggi District, Balangan Regency, South Kalimantan Province, from March 2018 - May 2019. This experiment used a single randomized block design (RBD), the factor studied was the administration of various doses of guano fertilizer (G) consisting of 4 levels , namely: g1 = 10 tons. ha-1 is equivalent to 3.3 kg. 1, g2 = 15 tons. ha-1 is equivalent to 4.95 kg. 1, g3 = 20 tons. ha-1 is equivalent to 6 , 6 kg. -1, g4 = 25 tons. ha-1 is equivalent to 8.25 kg. -1. Each experimental treatment consisted of 4 combinations and repeated 6 times, so that 24 experimental units were obtained. Where each experimental unit consists of 2 plants so that the whole plant has 48 plants. The results showed the growth of plant height aged 2, 3 and 4 month after planting (MAP); number of leaves aged 4 MAP; stem diameters 2, 3 and 4 showed a response to the growth of muli banana plants against various doses of guano fertilizer on podsolic fields. In generative growth only affects many fruits per comb, while at flowering time, harvest age, bunch length and many combs do not respond to the administration of various doses of guano fertilizer on podsolic fields. The best dose of guano fertilizer was g4 (25 ton.ha-1) for the growth of mauli banana plants on podsolic fields.